Evolution of public policies on natural disasters in brazil and worldwide - Kuhn, Caiubi E. S. [UNESP]; Reis, Fábio A. G. V. [UNESP]; DE OLIVEIRA, Vinicius G. [UNESP]; Cabral, Victor C. [UNESP]; Gabelini, Beatriz M. [UNESP]; Veloso, Vinicius Q. [UNESP] (FapUNIFESP (SciELO), 2022)
This work aims to carry out an analysis of the evolution of the civil defense protection policy in Brazil, as well as to present an overview of research related to public policies on natural disasters in the world. The research was developed by documentary analysis of Brazilian policies on the protection of civil defense and bibliometric analysis of the global data. The evolution of public policy on natural disasters in Brazil was divided into four different moments: a) military civil defense (1942-1946), b) disaster assistance policy (1967-1988), c) Civil Defense system in construction (1988-2005), and d) consolidation of the civil defense system (2005-to the present). The structuring of public policy reflected in 4 different stages in relation to the recording of information about disasters. Bibliometric analysis showed that the first works related to public civil defense policies in the world appeared only in 1980, and are mainly concentrated in the United States, which accounts for 42.56% of the works, while Brazil is the 6th country with 3.76% of global searches. Thus, it is possible to conclude that public policies and databases have a recent evolution both in Brazil and in the world, especially in developing countries.
Keywords: Brazil; database; natural disasters; public policies